The Influence of Halal Industry on Increasing Economic Growth in Islamic Countries - Mustofa, Hafidz Zainul (EQUILIBRIUM, 2024)
This study aims to analyze the halal industry's influence on economic growth in Islamic countries. The research gap in this study is that previous studies have indicated a diverse influence of halal industry variables on economic growth. Therefore, this study aims to provide a deeper understanding of the role of the halal industry in enhancing economic growth in Islamic countries. This study is quantitative research using secondary data categorized as panel data. The data consist of annual figures on Islamic Finance, Halal Food, Halal Travel, Halal Fashion, Halal Media and Recreation, and Economic Growth from 2014 to 2020 in 10 Islamic countries, obtained from the State of the Global Islamic Economy (SGIE) Report and the World Bank. The data analysis technique used is Panel VECM. The study results show that only the Islamic Finance variable positively affects economic growth in the short term. In contrast, the other variables show no effect or a negative effect on economic growth.